A Mixed Ligand Platinum(II) Complex: Spectral Analysis, Crystal Structure, Steric Demand of the Ligand, and Bioactivity of cis‐[Pt(PPh3)2(L1‐O, S)]PF6 (L1‐O, S = N, N‐Morpholine‐N′‐benzoylthiourea). Issue 21 (24th May 2019) - Pérez, Hiram; Ramos, Raúl; Plutín, Ana M.; Mocelo, Raúl; Erben, Mauricio F.; Castellano, Eduardo E.; Batista, Alzir A.
Abstract : A novel mixed platinum(II) complex with general formula [Pt(PPh3 )2 (L 1 ‐ O, S )]PF6 has been synthetized and characterized by elemental analysis, molar conductivity, and by IR and NMR ( 1 H, 13 C and 31 P) spectroscopic methods. The crystal structure has been determined by single‐crystal X‐ray crystallography. The molecule presents an almost ideal square‐planar geometry, and the crystal is stabilized by weak C–H··· O and C–H··· F hydrogen bonds, and C–H··· π stacking interactions. The steric congestion of ligands is described by "exact" cone and solid cone angles, and the percentage of metal surface shielded by the ligands. The results are compared to closely related palladium complexes. The X‐ray structure revealed the proximity of the ortho phenyl proton of one PPh3 ligand to platinum(II) showing rare intramolecular C–H··· Pt anagostic binding interaction. The title complex was determined to be active against tumor cells, and it also showed a moderate inhibitory action against mycobacterium tuberculosis . Abstract : A new platinum(II) complex with triphenylphosphine and benzoylthiourea ligands has been synthetized. The structure was determined by X‐ray diffraction showing almost perfect square‐planar geometry. Calculations of steric descriptors revealed sterically congested complexes. Furthermore, a rare intramolecular anagostic C–H··· Pt interaction was detected. The complex presents interesting biological activity.